The Size and Effectiveness of Automatic Fiscal Stabilizers in Latin America - Suescún, Rodrigo (World Bank, Washington, DC, 2012)
This paper measures the size of automatic fiscal revenue stabilizers and evaluates their role in Latin America. It introduces a relatively rich tax structure into a dynamic, stochastic, multi-sector small open economy inhabited by rule-of-thumb consumers (who consume their wages and do not save or borrow) and Ricardian households to study the stabilizing properties of different parameters of the tax code. The economy faces multiple sources of business cycle fluctuations: (1) world capital market shocks; (2) world business cycle shocks; (3) terms of trade shocks; (4) government spending shocks; and (5) nontradable and (6) tradable sector technology innovations. Calibrating the model economy to a typical Latin American economy allows the evaluation of its ability to mimic the region's observed business cycle frequency properties and the assessment of the quantitative relationship between tax code parameters, business cycle forcing variables, and business cycle behavior. The model captures many of the salient features of Latin America's business cycle facts and finds that the degree of smoothing provided by the automatic revenue stabilizers-described by various properties of the tax system-is negligible. Simulation results seem to suggest an invariance property for middle-income countries: the amplitude of the business cycle is independent of the tax structure. And government size-measured by the GDP ratio of government spending-plays the role of an automatic stabilizer, but its smoothing effect is very weak.